Analisa Produk Tabungan BSI dalam Menarik Minat Nasabah - Rachmad Nor Firman; Siti Ilfiah (Tasharruf : Journal of Islamic Economics and Business, 2022)
Bank Syariah Indonesia Pasuruan Branch is one of the banks operating based on sharia principles that offers products for raising funds and distributing funds, one of which is BSI savings. This BSI savings account is based on sharia principles with a mudharabah muthlaqah contract. This study uses primary data and secondary data. The results showed that the marketing strategy of BSI's savings products was to attract customers' interest. Bank Syariah Indonesia Pasuruan Branch has been running well, from promoting, socializing, distributing brochures and participating in certain events. In addition, the existence of Bank Syariah Indonesia Pasuruan Branch is very helpful for customers to open various kinds of savings provided by Bank Syariah Indonesia Pasuruan Sub-Branch Office.